Temporal arteritis presenting with scalp ulceration - Monteiro, C (2008)
We report the case of a 75-year-old-woman who presented with bilateral scalp ulcerations and blindness, accompanied by severe headache and scalp tenderness, due to bilateral temporal arteritis without systemic involvement. A biopsy taken from the border of an ulceration showed evidence of giant cell arteritis. She was treated with oral prednisone, 60 mg per day. The ulcerations healed in a few weeks but the vision loss was irreversible. This case highlights for temporal arteritis the importance of accurate and timely diagnosis as well as the need for prompt therapy with systemic steroids in order to avoid major complications, namely loss of vision. It also demonstrates that scalp necrosis and ulcerations are skin signs associated with a poor prognosis.